Perhitungan Sinyal Pada Simpang Dengan Metode Webster - Irma Wirantina Kustantrika (KILAT, 2015)
The main factor that effect the regulation to traffic light, especillly at the intersection is the large volume of vehicles. If have more vehicles are passing, they will have a long queue of vehicle pass through it. This means it needed the green light at the traffic light with sufficient time, so that the volume of the vehicle at the intersection can be reduced or even entirely passed. Related to the timing of the traffic light, it is necessarry to have a automatic control system that can be used to control it. In the timing of the traffic lights optimally at intersections, the data obtained are processed by using the method of Webster, and then conducted an analysis the data of the processing results. From the data processing volume of traffic density, then used as input data to control the timing of traffic light.